Potentialities of the Huamán church as a structuringelement of the strengthening of local identity - Cabada Acevedo, Daniela (2019)
In this article there are analyzed the potentials that there possesses the church Huaman as structuring element of the local identity, since by means of the social appropriation of the heritage a plurality of individuals is recognized like belonging to the same village and to the same territory. This way the identity fortifies and a sense of belonging is generated; therefore, the social appropriation of the heritage also can be understood as the foundation that allows to construct the unit in the diversity and, therefore, generator of new identities. The 89,8 % of the population thinks that the Church Huaman presents a sum of potentials, both historical and patrimonial and architectural that allow it to turn into an structuring axis of the local identity and the collective memory of the district. The church congregates many persons, not only on the religious part, but for the diversity of activities that there take place; these potentials do that the same one is a dynamic element and catalyst of the local identity of the district. The identity is the old territory of the heritage, between the aims recognized by most of patrimonial actions that are realized in these areas, this construction of the local identities, as autodefinition of one we.